2003
DOI: 10.1523/jneurosci.23-05-01688.2003
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Spinal Cord Glutamate Transport Capacity and Reduced Sensitivity to Riluzole in a Transgenic Superoxide Dismutase Mutant Rat Model of Amyotrophic Lateral Sclerosis

Abstract: We characterized synaptosomal glutamate transport activity in a recently developed transgenic rat model of amyotrophic lateral sclerosis (ALS) overexpressing the G93A Cu(2+)/Zn(2+) superoxide dismutase (SOD1) mutation. Using spinal cord synaptosomes, a significant reduction (43%) in the maximal velocity for high-affinity, Na(+)-dependent glutamate uptake was observed at disease end stage in G93A rats compared with age-matched controls. Similarly, a 27% reduction in maximum velocity (V(max)) was measured at dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 23 publications
6
80
0
Order By: Relevance
“…In mutant SOD1 mice, several studies have shown decreased EAAT2 protein and downregulation of glutamate-transport activity in affected CNS areas (9,15,20,23,41,151,153,155). Similar results are found in the SOD1-G93A and H46R transgenic rats (41, 68) (see also Fig.…”
Section: Astroglia Dysfunction In Als Occurs Through Different Synergsupporting
confidence: 74%
See 2 more Smart Citations
“…In mutant SOD1 mice, several studies have shown decreased EAAT2 protein and downregulation of glutamate-transport activity in affected CNS areas (9,15,20,23,41,151,153,155). Similar results are found in the SOD1-G93A and H46R transgenic rats (41, 68) (see also Fig.…”
Section: Astroglia Dysfunction In Als Occurs Through Different Synergsupporting
confidence: 74%
“…Another possibility is that, although EAAT2 could be properly translated and expressed, it loses function in ALS. This hypothesis is supported by the evidence that a lower V max for EAAT2 is measured in mutant SOD1 animal models (41). In addition, reactive oxygen species (ROS) formed in motor neurons after glutamate-receptor activation seem to be able to diffuse out of the motor neurons and induce oxidation and disruption of EAAT2-mediated glutamate uptake in neighboring astrocytes (108,109).…”
Section: Foran and Trottimentioning
confidence: 91%
See 1 more Smart Citation
“…However, this area is controversial in terms of when astrogliosis occurs and whether it precedes or accompanies dysfunction of motoneurons (Barbeito et al, 2004;Boillee et al, 2006;Maragakis and Rothstein, 2006). Although motoneurons were intact histologically and physiologically when there was marked astrogliosis with loss of EAAT2 in the SOD1 mutant rat model of ALS (Howland et al, 2002), other studies do not show a presymptomatic loss of EAAT2 (Bendotti et al, 2001;Dunlop et al, 2003). Overall, these data and the evidence for EAAT2 loss in human and animal models of ALS (Barbeito et al, 2004;Boillee et al, 2006) strongly implicate an astrocytic excitotoxic component in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Riluzole is the only Food and Drug Administration-approved drug for the treatment of amyotrophic lateral sclerosis and has been reported to prevent excitatory neurotransmitter release from presynaptic nerve terminals by a reduction of cytosolic Ca 2ϩ , as well as stimulated transmitter clearance from the synapse (Azbill et al, 2000;Dunlop et al, 2003;Wang et al, 2004). It was also discussed as treatment for cerebellar ataxias (Romano et al, 2015).…”
Section: Chac Neurons Show Elevated Synaptic Activitymentioning
confidence: 99%